The Effect of Training Methods and Leg Muscle Power Explosion Toward Kicking Skills in Pencak Silat - Sudirman, Ridwan; Asmawi, Moch; Hanif, Sofyan; Dlis, Firmansyah; Saputra, Surya Adi (Journal of Education, Health and Sport, 2019)
The purpose of this study was to determine the difference in effect between the Plyometric training method, the Maxex training method and the Circuit training method, with leg muscle power explosion toward kicking skills in the Pencak Silat. This research was conducted on students of the Physical Education Program in STKIP Setiabudhi Rangkasbitung, Banten Province. This research uses a 3x2 Level Design Treatment by factorial. The sample consisted of 60 students. Data analysis techniques used the two-way variance (ANOVA) and then used the Tuckey test at the significance level α = 0:05. The results of this study show that: 1) The plyometric training method has better influence on the circuit training method on the Pencak Silat kicking skills in the student group. 2) the plyometric training method is better in influence than the maxex training method on the Pencak Silat kicking skill on the student group, 3 ) The circuit training method has no significant effect compared to the maxex training method on the Pencak Silat kicking skills in the student group, 4) There is an interaction between the training method, the leg muscle power explosion and the Pencak kicking skills.